A critique of national solidarity in transnational organ sharing in Europe. Issue 1 (21st December 2017) - Tretyakov, Konstantin
Abstract: In this article, I critically examine the principle of national solidarity in organ sharing across national borders. More specifically, I analyse the policy foundations of solidarity in the transnational allocation of organs and its implementation in the system of national balance points adopted in Europe. I argue that the system of national balance points is based on statist collectivism and therefore is oriented more toward collective, rather than individual welfare. The same collective welfare rationale is also evident from leading policy statements about self-sufficiency in organ donation that seem to assume that cross-border organ sharing can be wrong if collective welfare is violated. This collectivist system of organ sharing can produce unjust results to individual candidates for organ transplantation. I propose several measures to reform the existing solidarity-based framework for the procurement and allocation of organs in order to balance the collective and the individual welfare of the donors and recipients of organs. I also discuss the implications of adopting that proposal.